Brain Natriuretic Peptide Production and Secretion in Inflammation - Tsuneo Ogawa; Adolfo J. de Bold (Journal of Transplantation)
Gene expression and secretion of the cardiac polypeptide hormones atrial natriuretic factor (ANF) and brain natriuretic peptide (BNP) are simultaneously upregulated in various cardiac disorders such as congestive heart failure, ischemic heart disease, and hypertensive heart disease, in which hemodynamic or neuroendocrine changes are key components in the progression of disease. However, during acute cardiac allograft rejection, plasma BNP levels are increased but not those of ANF. Successful treatment of the rejection episode decreases the elevated plasma BNP to prerejection values suggesting that substances related to inflammation may selectively influence BNP gene expression. Indeed, cytokines such as TNFα and IL-1β selectively stimulate cardiac BNP at the transcriptional and translational levels in cardiomyocyte cultures without affecting ANF. This selective BNP increase is seen in vivo, in addition to acute cardiac allograft rejection, in several circumstances where inflammation significantly contributes to the pathogenesis of disease such as in sepsis and in acute myocarditis.